Electrical conductivity, optical properties and mechanical stability of 3, 4, 9, 10-perylenetetracarboxylic dianhidride based organic semiconductor. (May 2015) - Pandey, Mayank; Joshi, Girish M.; Deshmukh, Kalim; Nath Ghosh, Narendra; Nambi Raj, N. Arunai
Abstract: The 3, 4, 9, 10-perylenetetracarboxylic dianhydride (PTCDA) doped polymer films were prepared with Polypyrrole (PPy) and Polyvinyl alcohol (PVA) polymers by solution-casting. The change in structure and chemical composition of samples was identified by XRD and FTIR respectively. The UV–visible spectroscopy demonstrates the optical characteristics and band gap properties of sample. The homogeneous morphology of sample for higher wt% of PTCDA was examined by atomic force microscopy (AFM). The differential scanning calorimetry (DSC) results demonstrate the decrease in melting temperature ( T m ) and degree of crystallinity ( χ c %) of polymeric organic semiconductor. The mechanical property demonstrates the high tensile strength and improved plasticity nature. Impedance spectroscopy was evaluated to determine the conductivity response of polymeric organic semiconductor. The highest DC conductivity (2.08×10 −3 S/m) was obtained for 10 wt% of PTCDA at 140 °C. The decrease in activation energy ( E a ) represents the non-Debye process and was evaluated from the slope of ln σ dc vs. 10 3 /T plot. Graphical abstract: Highlights: The PTCDA doped PPy/PVA polymer organic semiconductor was synthesized. AFM micrographs represent the homogeneity at higher concentration of PTCDA in polymer organic semiconductor. Good mechanical stability and plasticity nature of polymer organic semiconductor was obtained for 10 wt% of PTCDA. DSC thermograms demonstrate the change in melting peaks and crystallinity nature for different wt% of PTCDA in polymer organic semiconductor. Impedance spectroscopy technique was used to evaluate electrical conductivity.